2006
DOI: 10.1243/09544070jauto205
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Diesel Engine Fuelled with Rapeseed Oil Methyl Ester and Ethanol. Part 3: Combustion Processes

Abstract: In Part 1 of the paper efficiency and emissions of the engine fuelled with rape oil methyl ester (RME) and ethanol were presented and discussed. In the second part of the paper a comparison of emissions and brake fuel conversion efficiency of the engine for two base fuels, diesel fuel and rape oil ethyl ester, was carried out. In this paper, Part 3, combustion processes are investigated. Experiments were carried out on the same single-cylinder direct injection compression ignition engine as in Part 1. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
1
8
0
3
Order By: Relevance
“…The authors of this paper showed that CO and hydrocarbon (HC) emissions are higher than those of diesel mode but NO x and smoke emissions simultaneously decrease remarkably. Similar results were also presented by Kowalewicz …”
Section: Introductionsupporting
confidence: 91%
“…The authors of this paper showed that CO and hydrocarbon (HC) emissions are higher than those of diesel mode but NO x and smoke emissions simultaneously decrease remarkably. Similar results were also presented by Kowalewicz …”
Section: Introductionsupporting
confidence: 91%
“…Os picos encontrados para a carga de 37,5 kW foram de: 86,1 J/ºCA (IB7E30), 81,6 J/ºCA (IB7E25), 76,5 J/ºCA (IB7E20), 70,3 J/ºCA (IB7E15), 61,9 J/ºCA (IB7E10), 54,7 J/ºCA (IB7E5) e 49,1 J/ºCA (B7E0). Diversos autores [5,7,10,12] encontraram resultados semelhantes, com redução da pressão em cargas baixas e aumento em cargas altas, além de aumento do pico da taxa de liberação de calor com o uso de etanol.…”
Section: Figura 5 -Pressão No Interior Do Cilindro Em Função Do Combuunclassified
“…Pesquisas para aumentar a eficiência de conversão do combustível e reduzir os níveis de emissões são realizadas por modificações construtivas, controle da formação da mistura ou modificação dos combustíveis [3]. A emissão de NOX e MP é um dos maiores problemas de poluição das grandes cidades, tornando a busca por combustíveis menos poluentes cada vez mais intensa [4][5][6][7].…”
Section: Introductionunclassified
“…Os motores diesel têm alta eficiência de conversão de energia, elevado torque em relação aos motores que têm funcionamento regido pelo Ciclo Otto e oferecem vantagens sob o aspecto de knock e de consumo de combustível devido à alta taxa de compressão [4][5][6]. Entretanto, em contraponto à considerável eficiência, emitem elevados níveis de material particulado e NOX -elementos responsáveis por um dos maiores problemas de poluição contemporâneo [7][8][9][10]. Já o etanol surge como uma das melhores alternativas à adoção de um combustível renovável capaz de substituir os derivados do petróleo.…”
Section: Introductionunclassified